Contribution of local committees of the special meeting on agricultural industry in the development of the fundamentals of the new agricultural policy in the early 20th (on the materials of Uman county) - Svyaschenko, Zinaida (Ukrainian Peasant, 2021)
Introduction. The article analyzes the activities of the Uman County Committee of the Special Meeting on the needs of the agricultural industry. It is stated that the local committees have generally done a titanic job, providing the Special Meeting with mostly objective information about the problems in agriculture. Their work was fi nished in 1903 with the publication in the same year of 58 volumes of «Proceedings of Local Committees». The papers played a prominent role in the work of the Special Meeting. On the one hand, they allowed to form a holistic view of the state of agriculture in different regions of the Russian Empire. On the other hand, they were a kind of evidence base during the discussion of issues and the adoption of appropriate decisions during the meetings of the Special Meeting. Purpose. Сlarifi cation of regional features in the activities of local committees of the Special Meeting on the needs of the agricultural industry and their contribution to the development of the foundations of the new agricultural policy in the early twentieth century. on the materials of the Uman County Committee. Results. It is noted that the Uman County Committee considered a number of issues related to the improvement of agriculture in the region. Among them are the state of public education, veterinary care, the development of distilling, the need to combat ravines, agricultural pests, pollution of water bodies by sugar factories.The members of the committee also paid attention to the need for meteorological observations and the establishment of meteorological stations, the establishment of agricultural societies. According to the members of the committee, fi res, impassability, etc. were a signifi cant problem for Uman County. Issues related to lending to small farmers played a signifi cant role in the work of the committee. The views of the Uman County Committee on the existence of the community are analyzed and it is noted that the members of the Uman County Committee analyzed in detail the negative consequences of the existence of communal land tenure in the region. While fully sharing the views of the peasants, the members of the committee agreed that only with the liquidation of the community could improve the situation of the peasants. The members of the committee preferred the development of the farm in the region. Conclusion. That the need to reorganize agricultural policy was perceived in its own way by the members of the committee, however, they noted that in order to overcome the crisis of agriculture, fi rst of all it is necessary to eliminate cultural, legal, fi nancial and economic problems.